PROSEDUR PENGADAAN BARANG DI EMERSIA HOTEL & RESORT BATUSANGKAR - Rahmah, Ulfa (journal of residu, 2019)
This research aims to determine the procedure for procurement of goods at Emersia Hotel & Resort Batusangkar. This type of research is descriptive research with qualitative methods. Data collection techniques used were interview, observation, and documentation methods. The data analysis technique used is qualitative data analysis. From the results of the study found several things related to the procurement procedure at Emersia Hotel & Resort Batusngkar, they were: Often other departments such as Housekeeping, Marketing and Kitchen make Purchase Requests (PR) not according to procedures, lack of communication between Purchasing and Kitchen and Engineering thus causing double orders on suppliers, as well as lack of communication with certain suppliers, causing information ignorance that some prices of goods rise.